EFFECTS OF GAMMA IRRADIATION ON ACTIVE COMPONENTS, FREE RADICALS AND TOXICITY OF CASSUMUNAR GINGER RHIZOMES - Thongphasuk, Piyanut; Thongphasuk, Jarunee; Bavovada, Rapepol; Chamulitrat, Walee (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: To study the effects of gamma irradiation (10 and 25 kGy) on volatile oil constituents, total phenolic content, and free radical scavenging activity of cassumunar ginger rhizomes. Moreover, the effects on toxicity were investigated on both non-irradiated and irradiated samples, and accompanied by measurements of free radical content. Methods: Electron paramagnetic resonance spectroscopy (EPR) and GC-MS were used to determine free radicals and active compounds in essential oils, respectively. Toxicity was estimated using Toxi-Chromo Test. Total phenolic content and Antioxidant properties were determined using the Folin–Ciocalteu and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, respectively. Results: Irradiation at the doses of 10 and 25 kGy significantly (P < 0.05) increased free radicals in cassumunar ginger rhizomes. However, the volatile oils, total phenolic content, antioxidant activity and toxicity were not significantly (P > 0.05) affected by the irradiation doses. Conclusion: The present results suggest that gamma irradiation at the doses up to 25 kGy can safely be used to sanitize dried cassumunar ginger rhizomes.